Tracking sub-page components in document workflows - Ollis, James A.; Bagley, Steven R.; Brailsford, David F. (Association for Computing Machinery, 2008)
Documents go through numerous transformations and intermediate formats as they are processed from abstract markup into final printable form. This notion of a document workflow is well established but it is common to find that ideas about document components, which might exist in the source code for the document, become completely lost within an amorphous, unstructured, page of PDF prior to being rendered. Given the importance of a component-based approach in Variable Data Printing (VDP) we have developed a collection of tools that allow information about the various transformations to be embedded at each stage in the workflow, together with a visualization tool that uses this embedded information to display the relationships between the various intermediate documents. In this paper, we demonstrate these tools in the context of an example document workflow but the techniques described are widely applicable and would be easily adaptable to other workflows and for use in teaching tools to illustrate document component and VDP concepts.